Penentuan Kesehatan DAS Welang Sesuai Nilai Daya Dukung DAS Berdasarkan Kriteria Lahan - Prameswari, Anindya Hayu; Maroeto, Maroeto; Purwadi, Purwadi (Jurnal Solum, 2023)
The availability of land is dwindling along with the high population growth rate in each part of the Welang watershed, which has resulted in the health of the Welang watershed declining. Assessment of the health of the Welang watershed based on land criteria is expected to be able to determine the ability of the Welang watershed to provide for the needs of the community around the watershed. This study aims to determine the management and the condition of the carrying capacity of the watershed in terms of land criteria. Determination of watershed health was done by assessing the value of watershed carrying capacity according to the Regulation of the Minister of Forestry of the Republic of Indonesia Number: P.61/Menhut-II/2014 concerning Monitoring and Evaluation of Watershed Management. The carrying capacity value is reviewed based on land criteria, including: a) the percentage of critical land (PCL) through the calculation of critical land area, b) the percentage of vegetation cover (PVV) through the calculation of permanent vegetation area and c) the erosion index (EI) using the USLE approach. The Welang watershed is divided into upstream, middle and downstream areas of Bromo and Arjuno,. The results show that the carrying capacity of each part of the watershed is poor to moderate. The Arjuno upstream with the highest value of 50 is classified as bad class according to the percentage of PCL of 38.44%, PVV 66.92% and IE 1.88 tons/ha/year. Upstream Bromo has a value of 47.5 which is classified as poor class according to the PCL value of 28.10%, PVV 38.44% and EI 0.15 tons/ha/year. The downstream watershed has a value of 40, which is classified as medium class according to the percentage of critical land value of 0%, PVV 2.07% and EI 0.74 tons/ha/year and middle class has the lowest value 37.5 which is classified as medium class according to the PCL value of 6.44%, PVV 15.87% and EI 0.74 tons/ha/year. Based on the high PCL values in the upstream and middle areas which are classified as high, it can be concluded that the carrying capacity value of Arjuno and Bromo watershed is classified into the poor class as a result of the PCL values in the upstream and middle areas which are classified as high.Keywords: Carrying capacity, Erosion Index, Watershed